Mengevaluasi Tata Kelola Keuangan Syariah dan Zakat di Indonesia dan Pakistan pada Periode 2010 - 2024 melalui Analisis Komparatif untuk Membangun Kerangka Tata Kelola Syariah yang Kuat - Mujahid Hussain; Khadija Aziz (Muttaqien, 2026)
Islamic finance and zakat governance are crucial instruments for fostering financial inclusion and poverty alleviation in Muslim-majority countries. Although both Indonesia and Pakistan constitutionally recognize Islamic principles, they employ distinct institutional approaches, and comparative studies regarding their effectiveness and socio-economic impact remain limited. This research aims to conduct a comparative analysis of the development of Islamic finance and zakat governance in Indonesia and Pakistan (2010 - 2024) to formulate a robust Shariah governance framework that serves as a primary foundation for socio-economic strengthening. Employing a qualitative-comparative approach and doctrinal analysis of constitutions, regulations, and institutional reports, the study reveals that Indonesia possesses an advantage through an institutional system that integrates commercial and social finance (zakat and waqf), resulting in more measurable and effective socio-economic impacts. Conversely, while Pakistan possesses a strong jurisprudential foundation, it faces challenges regarding institutional fragmentation and weak policy coordination in optimizing zakat. The study concludes that strengthening governance, institutional transparency, and regulatory harmonization is essential to accelerate the equitable distribution of welfare. This research contributes a blueprint for an adaptive Shariah economic governance framework designed to foster comprehensive and sustainable socio-economic empowerment within Muslim nations.